Fetal Growth Trajectories and Their Association with Maternal, Cord Blood, and 5-year Child Adipokines - H. C. Bartels; A. A. Geraghty; E. C. O’Brien; A. Kranidi; J. Mehegan; C. Yelverton; C. M. McDonnell; F. M. McAuliffe (Journal of Nutrition and Metabolism)
Background. The growth of the fetus is a complex process influenced by multiple factors. Studies have highlighted the important role of biochemical growth markers such as leptin and adiponectin on fetal growth. Objective. To compare fetal growth trajectories with biochemical growth markers from maternal blood samples at 28 weeks’ gestation, cord blood samples at birth, and in child blood samples at 5 years of age from mother-infant pairs who were part of the longitudinal ROLO study. Methods. 781 mother-infant pairs from the ROLO and ROLO Kids study were included. Ultrasound measurements and birth weight were used to develop fetal growth trajectory groups for estimated abdominal circumference and estimated weight. Blood serum levels of leptin, adiponectin, insulin, TNF-alpha, and IL-6 from maternal, cord, and 5-year child samples were recorded. ANOVA and chi-square tests were applied to test the associations between fetal growth trajectory membership and maternal and child biochemical growth indicators. The influence of child sex was also investigated. Results. Male sex was associated with a faster weight trajectory compared to females (p=0.001). At 28 weeks’ gestation, maternal leptin levels were significantly higher in mothers with a fetus on a slower estimated abdominal circumference trajectory compared to fast (25616 [IQR: 11656.0 to 35341.0] vs. 14753.8 [IQR: 8565.4 to 24308.1], p<0.001) and maternal adiponectin levels were lower in fetuses on a slower estimated abdominal circumference trajectory compared to a fast trajectory (22.4 [IQR: 13.6 to 35.9] vs. 27.6 [IQR: 17.6 to 46.3], p=0.027). No associations were noted with inflammatory markers. No associations were identified between fetal growth trajectories and growth markers at 5 years of age. Conclusions. This study shows that male sex is associated with an accelerated estimated weight trajectory. Furthermore, high leptin and low adiponectin in maternal serum in late gestation are associated with a slower fetal growth trajectory. No associations were identified with blood growth markers after pregnancy.